Penerapan metode praktikum berbasis bahan alam dalam pembelajaran kimia untuk meningkatkan hasil belajar siswa pada materi reaksi redoks - Loriana Tiak; Djefri Tani; Joice Dorsila Susana Caroles (Chemistry Department, Universitas Negeri Manado, 2019)
The purpose of this study was to determine the improvement in learning outcomes of class X students in East Halmahera 9 High School on redox reaction topic by using natural product praticum methods in chemistry learning. This research is a preexperimental study with a One Group Pretest-Posttest Design. The population and sample are taken all students of class X with a total number of students of 20 people. The collected data is processed from the results of the pretes-posttest. Data were analyzed using the formula t-test the research hypothesis and obtained tcount> t table (19.49> 2.10). The results show that the average posttest value was greater than the average value of the pretest, so it can be concluded that student learning outcomes provided with natural product practicum methods influence student learning outcomes.